Democracia e educação: uma análise da crítica às políticas educacionais do Brasil (1995-2002) - Borges, Liliam Faria Porto (Universidade Federal de São Carlos, 2006)
The Brazilian marxist current educators who criticize the educational policies from the 1995 to 2002 Fernando Henrique Cardoso governments, in Brazil, start analysing about the circumstances of a neo-liberal government, strongly marked by the weight of international financial agencies which impose educational policies profiles that in order to guarantee the capitalist accumulation, these policies have a character of strong exclusion. We highlight Gaudêncio Frigotto and Pablo Gentili, as expressions from this group of educators. Thequestion they point out as fundamental is the lack of democracy in the relations between the State and society and also in the several social instances, that prevent from the possibility of the great majority of Brazilians characterize themselves as citizens. This work recognizes all the criticized elements as legitimate, but seek to problemize the format how to elaborate the critique itself, because there is in its formulations a bet in democracy and as an outcome, a belief in education as a social changing area, elements proper to the liberal thinking, thatreinforce the myth of a redempting school. Considering the affiliation of the authors to marxism, we indicate the inheritage of social-democracy and the determined use they make of marxism, as the closest identification with the theoretical formulation from the authors studied here.
Keywords: Brasil - educação; Política educacional; Democracia; Socialismo; Education; Democracy; Educational policy; Marxism; Social-democracy; CIENCIAS HUMANAS::EDUCACAO